State Street and the Old State House, ca. 1870-75 - Ward, Joseph and Son (Tufts Archival Research Center, 2005)
Street-level view west-southwest of State Street and the Old State House, which is located on State Street between Washington Street to the west and Devonshire Street to the east. Signage adorns the east elevation of the Old State House. Buildings lining the south-southeast side of State Street are included in the left-half of the carte-de-visite. The Boston Exchange Company Building, located at 49-57 State Street, lines the left edge of the image. Street lights, pedestrians and horse-drawn carriages are included in the carte-de-visite. 3 1/2 x 2 1/4, 3 15/16 x 2 3/8 overall Cartes-de-visite